The Influence of Organizational Culture on Employee Performance Through Job Satisfaction as an Intervening Variable: A Case Study of Roti Ajib Sumenep - Krisna Guntur Saputro; Rachmat Hidayat; Sri Rahayu (Majapahit Journal of Islamic Finance and Management, 2026)
In an increasingly changing and competitive business climate, organizations are required to have internal capacity to ensure their effectiveness and sustainability. One strategic resource that plays a crucial role is organizational culture. Conceptually and methodologically, this study adopts a multidimensional model of organizational culture and examines the causal relationships and mediating mechanisms (culture, job satisfaction, and employee performance). Furthermore, this study contributes to the academic literature on management and human resources in Indonesia, particularly regarding the dynamics of small-scale organizations.